2018
DOI: 10.1016/s2468-1253(18)30032-3
|View full text |Cite|
|
Sign up to set email alerts
|

Post-imaging colorectal cancer or interval cancer rates after CT colonography: a systematic review and meta-analysis

Abstract: St Mark's Hospital Foundation and the UK National Institute for Health Research via the UCL/UCLH Biomedical Research Centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 53 publications
(141 reference statements)
1
18
0
2
Order By: Relevance
“…63 These data translate to a low interval cancer incidence of 0.6 per 1000 person-years of follow-up, particularly encouraging given that only 7% of the interval cancers retrospectively reviewed in this study were truly occult. 62 These data support current CTC management strategies of not reporting diminutive polyps and the option of CTC follow-up for small polyps. Since most missed cancers at CTC were visible in retrospect, formal training and accreditation is warranted to ensure consistent high-quality practice (inter)nationally.…”
Section: Referral Thresholds and Diminutive Polypssupporting
confidence: 69%
See 1 more Smart Citation
“…63 These data translate to a low interval cancer incidence of 0.6 per 1000 person-years of follow-up, particularly encouraging given that only 7% of the interval cancers retrospectively reviewed in this study were truly occult. 62 These data support current CTC management strategies of not reporting diminutive polyps and the option of CTC follow-up for small polyps. Since most missed cancers at CTC were visible in retrospect, formal training and accreditation is warranted to ensure consistent high-quality practice (inter)nationally.…”
Section: Referral Thresholds and Diminutive Polypssupporting
confidence: 69%
“…Ultimately, the most important quality indicator of CTC management is the rate of interval cancer after negative CTC. A recent systematic review has shown this rate to be 4.4% in the published literature, 62 which compares favourably with colonoscopy (published rates 3-9%). 63 These data translate to a low interval cancer incidence of 0.6 per 1000 person-years of follow-up, particularly encouraging given that only 7% of the interval cancers retrospectively reviewed in this study were truly occult.…”
Section: Referral Thresholds and Diminutive Polypsmentioning
confidence: 91%
“…Two new European randomized trials [17,18] and an evaluation of follow-up [19] have shown detection rates for advanced neoplasia being similar to those of optical colonoscopy in asymptomatic individuals invited for screening. A systematic review has shown the rate of interval cancers after a negative CTC (4.5 %) compares favorably with that following optical colonoscopy (3 % -9 %) [20]. In a Japanese multicenter trial, including 1177 patients, sensitivities and specificities of over 90 % were achieved for detection of colorectal neoplasia > 9 mm by CTC [21].…”
Section: Radiological Imaging For the Diagnosis Of Colorectal Neoplasiamentioning
confidence: 99%
“…The literature is relatively clear regarding detection of established CRC: two meta-analyses have shown that CTC is approximately 96% sensitive for CRC [21,22], not significantly different from colonoscopy, which was 95% sensitive in one of these analyses [22]. Furthermore, a recent further systematic review has shown that identification of (initially undetected) CRC in the 3-year period following CTC is rare, only occurring in 4.4% of cases [23]. Since adenomas typically take many years or even decades to transition to carcinoma [24], these are likely to be due to missed CRC at the index CTC examination, entirely consistent with approximately 95% sensitivity for cancer.…”
Section: Diagnostic Accuracymentioning
confidence: 99%